United we stand: labour unions and human rights NGOS in the democratisation process in Nigeria (2004)
Human rights NGOs were the vanguard of the struggle for democratisation in Nigeria, but they had to forge alliances with labour unions and other groups to galvanise this process effectively. This paper explores the alliances between labour unions and NGOs in the struggle against military dictatorship in Nigeria to analyse how horizontal relationships have fared in exchanges within civil society. It argues that the exigencies of sustained political struggle throw up conflicts over issues of participation, accountability, and egalitarianism that in turn promote social capital within civil society by mitigating hierarchically structured and asymmetrical patterns of exchange among its members.